2017
DOI: 10.1002/hpm.2449
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with health care services at a national institute of ophthalmology

Abstract: Little is known about how patients in developing countries, such as Vietnam, are satisfied with eye care services. The purpose of this study was to assess the satisfaction with health services and its associated factors among patients attending a national institute of ophthalmology in Vietnam. In a cross-sectional study utilizing quantitative methods, 500 inpatients and their relatives attending a national institute of ophthalmology in Vietnam were approached for data collection. The results indicated that und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…Patient satisfaction is an important indicator of health care quality and often associated with greater adherence to medical technology, health service utilization, and health outcomes [19,20,21]. Huy and colleagues observed that satisfaction has a significant impact on patient retention, patient loyalty and influences the efficient delivery of quality in health care [22]. Furthermore, clients’ experience and opinions are important for improving healthcare services, shaping health policies and providing feedback on the quality, availability, and responsiveness of healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…Patient satisfaction is an important indicator of health care quality and often associated with greater adherence to medical technology, health service utilization, and health outcomes [19,20,21]. Huy and colleagues observed that satisfaction has a significant impact on patient retention, patient loyalty and influences the efficient delivery of quality in health care [22]. Furthermore, clients’ experience and opinions are important for improving healthcare services, shaping health policies and providing feedback on the quality, availability, and responsiveness of healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, analysis (average) of each observation was performed and given a colour, as reported in the tables in the results. Green indicates the highest score (5-6), yellow indicates a moderate score (3)(4) and red indicates the lowest score (1-2). All data were calculated (multiplied or divided; for example, 13/6 = 2.16666666666666 = 2.167) to show the percentages of the identified similarities and differences.…”
Section: C1: Privacy Company and Dignitymentioning
confidence: 99%
“…influences patients' and their relatives' experiences of healthcare, as do gender and localization [2]. Overall, patients rate their satisfaction rather low and describe dissatisfaction regarding the lack of beds and limited space within the stressful and overcrowded hospital environment [3,4]. According to Nightingale [5], five environmental aspects are important: Ventilation, clean water, an effective sewage system, and clean and bright rooms.…”
mentioning
confidence: 99%
“…Satisfaction is "the human experience of being filled and enriched by an experience" (Safaan, Elkhouly, & Ibrahem, 2015, p. 13300). Patient satisfaction, including the relationship between patients and healthcare providers in medical settings (Huy, Dung, Thang, & Hanh, 2017) is a significant contributing factor in improving health care process (Dunsch, Evans, Macis, & Wang, 2018). Patient satisfaction is broadly the expectations of a patient and whether those expectations are met or not (Sharma, 2017).…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…Patient satisfaction is broadly the expectations of a patient and whether those expectations are met or not (Sharma, 2017). Evans, Stanley, and Burrows (2009) Satisfaction is a key indicator in determining the quality of healthcare delivery (Ali, 2016;McMullen & Netland, 2013;Safaan et al, 2015;Verulava, Jorbenada, Karimi, Dangadze, & Barkalaia, 2018;Xesfingi & Voikis, 2016) as well as determining the response to patients' needs (Huy, et al, 2017). According to Huy et al (2017), satisfaction influences patient retention, clinical outcomes, patient loyalty, and consistent profitability.…”
Section: Patient Satisfactionmentioning
confidence: 99%